Evaluation of OCO‐2 X CO2 Variability at Local and Synoptic Scales using Lidar and In Situ Observations from the ACT‐America Campaigns. Issue 10 (18th May 2020) - Bell, Emily; O'Dell, Christopher W.; Davis, Kenneth J.; Campbell, Joel; Browell, Edward; Scott Denning, A.; Dobler, Jeremy; Erxleben, Wayne; Fan, Tai‐Fang; Kooi, Susan; Lin, Bing; Pal, Sandip; et al.
Abstract: With nearly 1 million observations of column‐mean carbon dioxide concentration (X CO 2 ) per day, the Orbiting Carbon Observatory 2 (OCO‐2) presents exciting possibilities for monitoring the global carbon cycle, including the detection of subcontinental column CO2 variations. While the OCO‐2 data set has been shown to achieve target precision and accuracy on a single‐sounding level, the validation of X CO 2 spatial gradients on subcontinental scales remains challenging. In this work, we investigate the use of an integrated path differential absorption (IPDA) lidar for evaluation of OCO‐2 observations via NASA's Atmospheric Carbon and Transport (ACT)‐America project. The project has completed eight clear‐sky underflights of OCO‐2 with the Multifunctional Fiber Laser Lidar (MFLL)—along with a suite of in situ instruments—giving a precisely colocated, high‐resolution validation data set spanning nearly 3, 800 km across four seasons. We explore the challenges and opportunities involved in comparing the MFLL and OCO‐2 X CO 2 data sets and evaluate their agreement on synoptic and local scales. We find that OCO‐2 synoptic‐scale gradients generally agree with those derived from the lidar, typically to ±0.1 ppm per degree latitude for gradients ranging in strength from 0 to 1 ppm per degree latitude. CO2 reanalysis products also typically agree to ±0.25 ppm per degree when compared with an in situ‐informed CO2 "curtain." Real X CO 2 features at local scales, however, remain challenging to observe and validate from space, with correlation coefficients typically below 0.35 between OCO‐2 and the MFLL. Even so, ACT‐America data have helped investigate interesting local X CO 2 patterns and identify systematic spurious cloud‐related features in the OCO‐2 data set. Key Points: OCO‐2 and lidar tend to agree on synoptic‐scale X CO 2 gradients, over a few hundred kilometers, to within 0.1 ppm per degree latitude There is very little agreement among tested data sets on smaller‐scale X CO 2 features, on the order of tens of kilometers The OCO‐2 X CO 2 data set contains some systematic spurious retrievals apparently due to 3D cloud effects, which should be addressed in the future